2017
DOI: 10.1080/08946566.2017.1352550
|View full text |Cite
|
Sign up to set email alerts
|

Professional quality of life of adult protective service workers

Abstract: Adult Protective Services (APS) workers are exposed to substantial occupational hazards and job stress, but these stressors are underdocumented. Therefore, we sought to describe APS workers' work environments and responses to occupational hazards and stressors, including compassion fatigue, burnout, and secondary traumatic stress. Survey data were gathered with closed-ended questionnaires administered to APS workers in an urban setting. Virtually all workers (97%) reported exposure to one or more environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…Focus group participants reported demonstrated benefits in their knowledge and associated skills from training on their work, ability to help clients, and feelings of safety in the field. Ghesquiere et al (2018) reported APS caseworkers were exposed to substantial occupational hazards and stressors that were often undocumented, and our findings supported the importance to train caseworkers on responding to them. Another important finding was that heavy caseloads, access to training, and local protocols and relationships with other service agencies were key obstacles to practice change.…”
Section: Discussionsupporting
confidence: 79%
“…Focus group participants reported demonstrated benefits in their knowledge and associated skills from training on their work, ability to help clients, and feelings of safety in the field. Ghesquiere et al (2018) reported APS caseworkers were exposed to substantial occupational hazards and stressors that were often undocumented, and our findings supported the importance to train caseworkers on responding to them. Another important finding was that heavy caseloads, access to training, and local protocols and relationships with other service agencies were key obstacles to practice change.…”
Section: Discussionsupporting
confidence: 79%
“…Adult/elder protective services (some states use adult protective services, whereas others use elder protective services, to refer to adults 18-64 and older adults 65þ) social workers are the first responders to any incidents involving adults at-risk of being abused (Ghesquiere, Plichta, McAfee, & Rogers, 2018). Adult/elder protective service workers serve older adults and those who suffer from neurocognitive disorders, adults (18þ) with disabilities, or those who are at risk of eviction (e.g.…”
Section: Adult/elder and Child Protective Services Rolesmentioning
confidence: 99%
“…Adult/elder protective service workers serve older adults and those who suffer from neurocognitive disorders, adults (18þ) with disabilities, or those who are at risk of eviction (e.g. Ghesquiere et al, 2018;Leon, Altholz, & Dziegielewski, 1999;Stiegel, 2006). Child protective services workers have similar duties, but their clients are under age 18.…”
Section: Adult/elder and Child Protective Services Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mediators were found to have high levels of distress at work, suggesting they were at risk. As in the studies by Cuartero-Castañer and Campos-Vidal (2019) and Ghesquiere et al (2018), self-care positively affected compassion satisfaction and helped reduce burnout and compassion fatigue. Our study confirms that self-care practices ultimately and positively impact the professional quality of life of those who engage in them.…”
Section: Discussionmentioning
confidence: 61%